2013
DOI: 10.1071/ch12404
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Phosphatidylcholine with Conjugated Linoleic Acid and Studies on Its Cytotoxic Activity

Abstract: Phospholipids with conjugated linoleic acid (CLA), which are potential lipid prodrugs, were synthesised. CLA was obtained by the alkali-isomerisation of linoleic acid and was subsequently used in the synthesis of 1,2-di(conjugated)linoleoyl-sn-glycero-3-phosphocholine in good (82 %) yield. 1-Palmitoyl-2-(conjugated)linoleoyl-sn-glycero-3-phosphocholine was obtained by a two-step synthesis in 87 % yield. All the compounds were tested in an in vitro cytotoxicity assay against two human cancer cell lines, HL-60 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 37 publications
3
28
0
1
Order By: Relevance
“…Moreover, this approach has already been successfully applied to the synthesis of LPCs by Servi et al (Fasoli, et al, 2006). When we applied this 9 approach to diol 6, we obtained trityl-protected LPEs 7'-17' in yields that were merely moderate (18-44%) compared to previously reported LPCs (Scheme 2) (Fasoli, et al, 2006;Niezgoda, et al, 2013). The results of these experiments are summarized in Table 1.…”
Section: Chemical Synthesis Of An Lpe Librarysupporting
confidence: 55%
See 1 more Smart Citation
“…Moreover, this approach has already been successfully applied to the synthesis of LPCs by Servi et al (Fasoli, et al, 2006). When we applied this 9 approach to diol 6, we obtained trityl-protected LPEs 7'-17' in yields that were merely moderate (18-44%) compared to previously reported LPCs (Scheme 2) (Fasoli, et al, 2006;Niezgoda, et al, 2013). The results of these experiments are summarized in Table 1.…”
Section: Chemical Synthesis Of An Lpe Librarysupporting
confidence: 55%
“…After deprotection, we observed regioselectivity ratios (2-LPE:1-LPE) of 3:1 to 7:3, with the exception of 3:2 for 15 (entry 9, Table 1). Even though these ratios are not as high as for the previously reported LPCs (Fasoli, et al, 2006;Niezgoda, et al, 2013), they are nevertheless acceptable, considering the aforementioned problematic acyl migration. Even if the acylation was highly regioselective, the acidic work-up should promote a 1,2-O-acyl migration and thus lower the selectivity.…”
Section: Chemical Synthesis Of An Lpe Librarymentioning
confidence: 72%
“…It is formed together with cis-9, trans-11 as the second major product of the alkaline isomerization of linoleic acid. [11] It has been observed that a difference in molecular structure of particular isomers can cause variation in their activity. For instance, the cis-9,cis-11 isomer showed the ability to inhibit more than 60 % of the breast cancer MCF-7 cell population, whereas cis-9,trans-11 CLA inhibited only 20 %.…”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR and 13 C NMR spectra of (4g) were analyzed according to earlier studies. 25 Esterification of (2,3-epoxypropyl)phosphonate (2) with palmitic acid anhydride was also tested. The reaction was carried out according to the procedure of Ali and Bittman.…”
Section: Introductionmentioning
confidence: 99%